2018
DOI: 10.1177/1367006918790808
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativeness – A necessary trait for interpreters? A study on temperament and character dimensions of experts in different fields

Abstract: Aims and Objectives: The aim of the present study was to investigate whether particular temperament and personality traits are more characteristic to interpreters’ expert performance than to expert performance in other fields. Design: To these ends, the Temperament and Character Inventory by Cloninger et al. (1994) and the distractibility scale of the Revised Dimensions of Temperament Survey by Windle (1992) were used. Data and Analyses: The data was gathered from two groups of interpreters (simultaneous and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Hampson, 2012). Nevertheless, rather than explaining short-term states, personality may be better at explaining long-term outcomes such as development of expertise (Hiltunen et al, 2019), health (Ferguson, 2013;Jokela et al, 2019), mental health problems (Ormel et al, 2013;Ervasti et al, 2019) and several other long-term outcomes such as salary (Gensowski, 2018). Neuroticism and rumination, the expected key trait variables in this study, have also been found to been associated with heart rate variability (M€ a€ att€ anen et al, 2019).…”
Section: Introductionmentioning
confidence: 70%
“…Hampson, 2012). Nevertheless, rather than explaining short-term states, personality may be better at explaining long-term outcomes such as development of expertise (Hiltunen et al, 2019), health (Ferguson, 2013;Jokela et al, 2019), mental health problems (Ormel et al, 2013;Ervasti et al, 2019) and several other long-term outcomes such as salary (Gensowski, 2018). Neuroticism and rumination, the expected key trait variables in this study, have also been found to been associated with heart rate variability (M€ a€ att€ anen et al, 2019).…”
Section: Introductionmentioning
confidence: 70%